2021
DOI: 10.1111/ijcp.14779
|View full text |Cite
|
Sign up to set email alerts
|

The combination of omega−3 fatty acids with high doses of vitamin D3 elevate A1c levels: A randomized Clinical Trial in people with vitamin D deficiency

Abstract: The High prevalence of vitamin D deficiency (VDD) and type 2 diabetes mellitus (T2DM) among Jordanians spread dramatically during the last decade. 1,2 This was related to an increased risk of T2DM in people with VDD. 3,4 There is no consensus yet about the possible therapeutic effect for VD 3 on glycaemic control in diabetics or prediabetics with VDD. However, some reports have pointed out that VD 3 supplementation may improve glycaemic control in diabetic patients, as well as pre-diabetic people with VDD. 5-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…(2017) demonstrated that short-term supplementation with omega-3 and vitamin D in GDM women could decrease TG and VLDL-C. Nevertheless, Barham et al. (2021) did not find any significant effect after supplementation with omega - 3 and vitamin D in vitamin D deficient participants.…”
Section: Discussionmentioning
confidence: 99%
“…(2017) demonstrated that short-term supplementation with omega-3 and vitamin D in GDM women could decrease TG and VLDL-C. Nevertheless, Barham et al. (2021) did not find any significant effect after supplementation with omega - 3 and vitamin D in vitamin D deficient participants.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, other trials reported a significant reduction in fasting blood glucose, insulin resistance, and HbA1c after supplementing the diet with dosage of n -3 PUFA ranging from 0.41 to 3 g/day for a follow-up of 8 weeks to 1 year as well [ 59 , 60 , 61 , 62 , 63 ] ( Table 3 ). One particular RCT conducted among patients with vitamin D deficiency reported a significant increase in HbA1c in the n -3 PUFA group after 8 weeks of supplementation with 0.3 g of n -3 PUFA daily and 50,000 IU of vitamin D weekly [ 64 ].…”
Section: Effects Of N -3 Pufa On Major Chronic Dis...mentioning
confidence: 99%